ANALYSIS OF EMPLOYEE PERFORMANCE IMPROVEMENT STRATEGIES FROM THE WORK ENVIRONMENT PERSPECTIVE AT PT. CITRA SAWIT MANDIRI LABUHANBATU DISTRICT - Ade Rizka Adilla; Lisa Iryani; Nanda Ameliany; Teuku Zulkarnaen; Sutriani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the employee performance improvement strategies implemented by PT. Citra Sawit Mandiri, specifically from a work environment perspective. A conducive work environment is believed to play a significant role in increasing employee morale, motivation, and productivity. The research method used is qualitative with a descriptive approach. Data were obtained through in-depth interviews with several employees and field foremen as well as documentation at the research location. The results show that employee performance improvement strategies in this company include routine work briefings, incentives, technical training, and periodic performance evaluations. However, the physical work environment conditions such as lighting, temperature, and work facilities in the field are still inadequate and are a complaint for some employees. In addition, the relationship between superiors and subordinates is also an important factor that influences work comfort. From this analysis, it can be concluded that performance improvement strategies will run optimally if balanced with improvements in the work environment, both physical and non-physical. This research is expected to provide input for companies in formulating more effective and sustainable human resource management policies.